2018
DOI: 10.1038/s41598-018-26094-0
|View full text |Cite
|
Sign up to set email alerts
|

The bony labyrinth of toothed whales reflects both phylogeny and habitat preferences

Abstract: The inner ear of toothed whales (odontocetes) is known to have evolved particular shapes related to their abilities to echolocate and move under water. While the origin of these capacities is now more and more examined, thanks to new imaging techniques, little is still known about how informative inner ear shape could be to tackle phylogenetic issues or questions pertaining to the habitat preferences of extinct species. Here we show that the shape of the bony labyrinth of toothed whales provides key informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…Similarly, a study using 3D geometric morphometrics of odontocete inner ear labyrinths found that the semicircular canals are not statistically significantly informative for ecological preference, whereas the cochlea alone is a decent proxy for habitat (Costeur et al. ). Riverine, coastal, and arctic environments all have different requirements for sound production and reception because of differences in spatial dimensions including pack ice; as Costeur et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, a study using 3D geometric morphometrics of odontocete inner ear labyrinths found that the semicircular canals are not statistically significantly informative for ecological preference, whereas the cochlea alone is a decent proxy for habitat (Costeur et al. ). Riverine, coastal, and arctic environments all have different requirements for sound production and reception because of differences in spatial dimensions including pack ice; as Costeur et al.…”
Section: Discussionmentioning
confidence: 99%
“…Riverine, coastal, and arctic environments all have different requirements for sound production and reception because of differences in spatial dimensions including pack ice; as Costeur et al. () found, the cochlea may be informative for certain aspects of sensory requirements in certain habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therian mammals (marsupials and placentals) show at least one full turn but can have more than three turns (e.g., 3.25 in domestic cats [Schellhorn, ], or 3.3 in whales [Ekdale, ]). Furthermore, the shape of the cochlear is phylogenetically informative in whales (toothless: Ekdale, ; toothed: Costeur et al, ).…”
Section: Introductionmentioning
confidence: 99%